Evaluation for additional work of sharing pile work between zone A and zone C – 05.04.18 - BUCG-ABC Joint Venture (BUCG-ABC JV) (Brac University, 2023)
This record consists of general correspondence regarding the evaluation for additional work of sharing pile work between zone A and zone C of BRACU new campus development project.